2014
DOI: 10.1016/j.yjmcc.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte autophagy and cancer chemotherapy

Abstract: Autophagy, an evolutionally conserved process of controlled cellular cannibalization, plays a vital role in cardiac physiology. Perturbations in cardiomyocyte autophagy contribute to the pathogenesis of a wide range of cardiac diseases, many of which culminate in heart failure. With recent advances in cancer chemotherapy and consequent improvements in cancer survival, drug-induced toxicity to the heart has assumed greater importance. As a number of prominent cellular pathways are critical to the survival of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 84 publications
(113 reference statements)
1
42
0
2
Order By: Relevance
“…Previous studies have addressed the possible contribution of changes in autophagic flux to doxorubicin cardiotoxicity; their findings, however, are conflicting 43, 44 . Autophagy has been reported to be either increased 812 or decreased 10, 13, 14 , based on in vivo and/or in vitro analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed the possible contribution of changes in autophagic flux to doxorubicin cardiotoxicity; their findings, however, are conflicting 43, 44 . Autophagy has been reported to be either increased 812 or decreased 10, 13, 14 , based on in vivo and/or in vitro analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated a unique role for defective cardiomyocyte autophagy in various cardiac anomalies such as cardiomyopathy and heart failure, as well as premature cardiac aging (6871). Basal autophagy and autophagic flux are crucial for cardiomyocyte homeostasis (72). Cardiomyocyte-specific Atg5 knockout mice developed dilated cardiomyopathy in adulthoods (71).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, an evolutionally conserved process of controlled cellular cannibalization, plays a vital role in cardiac physiology. Perturbations in cardiomyocyte autophagy contribute to the pathogenesis of a wide range of cardiac diseases, many of which culminate in heart failure [10]. LC3 is the only known protein that is specifically associated with all types of autophagic membranes, including phagophores, autophagosomes and autolysosomes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Perturbations in cardiomyocyte autophagy contribute to the pathogenesis of a wide range of cardiac diseases, many of which culminate in heart failure [10]. LC3 is the only known protein that is specifically associated with all types of autophagic membranes, including phagophores, autophagosomes and autolysosomes [10]. Therefore, the amount of LC3-II correlates well with the number of autophagosomes, which provides a good index of autophagy induction [9].…”
Section: Introductionmentioning
confidence: 99%